The visible dead: dolmens and the landscape in Early Bronze Age Jordan - Fraser, James (BAF-Online: Proceedings of the Berner Altorientalisches Forum, 2025)
Overview:Dolmens are usually described as part of a regional megalithic phenomenon that spanned the 5th-2nd millennia BC. However, this presentation assumes that most ‘dolmens’ are mis-identified. When strictly defined, dolmens better reflect a local funerary tradition of the 4th millennium BC.Definitions:The term dolmen includes a variety of features whose only similarity is their use of large stone slabs. This presentation defines a dolmen as a freestanding,rectangular chamber formed by two upright orthostats along each long side, and a single roof slab over the top. Dolmens have often been conflated with cairns. This presentation defines a cairn as a large pile of small stones. Such features may have contained a low, cist burial chamber; others may simply be piles of field clearance.Distribution:Dolmens, as defined above, concentrate within a limited area of the east rift escarpment of the Jordan Valley, consistent with a local funerary tradition.Chronology: Recent dolmen excavations have yielded assemblages that date exclusively to the EB I (c.3700-3000 BC). This talk examines the close spatial relationship between dolmens and EB I settlement sites in a discrete geographical zone.